Relationship between Ottoman and Albanian Culture as an Intercultural Example of Interaction (International Journal of Scientific Research and Management (IJSRM), 2019)
Islam and Ottoman cultures have had a significant impact on the Albanian culture from the 15th century to the present. Islam has also been a shield that protects Albanian culture from Slavic and Greek assimilations. Therefore, the Islamic culture has had a very strong influence on the components that formed Albanians’ social structure. It is possible to see the effects of Islamic culture on Albanians’ life styles, family cultures, death and marriage rituals, economic lives, legal relations and all mentality structures and the system of values ​​that constitute the society. It was not difficult to adapt to the Albanian culture especially for the Ottoman interpretation of Islam because these two cultures have been built similarly on the old Mediterranean cultural basin. It is possible to find many common values ​​between the two cultures. For example, the values ​​including tolerance, indulgence, freedom, and, most importantly, being against discrimination are the elements that made these two cultures closer and united to each other. It is sufficient to look at the history in order to understand how tolerant Albanians are about religion. They have been able to live together with three different religions in high tolerance for centuries. The level of tolerance is such that there are individuals of different religions in a tribe or even in a family. The Islamized Albanians can also maintain their traditions, customs and authentic lifestyles along with the Islamic culture.